High‐throughput liquid chromatography/mass spectrometry method for the quantitation of small molecules using accurate mass technologies in supporting discovery drug screening. (26th December 2012) - Ding, Xiao; Ghobarah, Hesham; Zhang, Xiaolin; Jaochico, Allan; Liu, Xingrong; Deshmukh, Gauri; Liederer, Bianca M.; Hop, Cornelis E. C. A.; Dean, Brian
<x xml:space="preserve">Abstract</x> RATIONALE Drug discovery samples are routinely analyzed using liquid chromatography/tandem mass spectrometry (LC/MS/MS) methods on triple quadrupole mass spectrometers employing multiple reaction monitoring (MRM). In order to improve analysis throughput, quantitation of small molecules on a quadrupole time‐of‐flight (QqTOF) instrument using TOF scan and high‐resolution MRM (MRM‐HR) modes was evaluated in this study. METHODS Cassette dosed plasma and brain samples from nine compounds were extracted using a protein precipitation method. Separation was achieved by reversed‐phase liquid chromatography. Mass spectrometric analysis was performed using TOF scan and high‐resolution MRM approaches on a QqTOF mass spectrometer with turbo‐ionspray ionization. Results were compared to those obtained on a triple quadrupole mass spectrometer. RESULTS The dynamic range varied depending on compounds and instruments and was similar between the MRM on QqQ and full TOF scan mode on QqTOF. Linear or quadratic regression and 1/x2 weighting were used. Resolution on the QqTOF instrument was around 32000 and mass accuracy was within 4.4 ppm. The MRM‐HR method showed better sensitivity compared to the TOF scan method, and was comparable to the MRM on a QqQ mass spectrometer. Assay accuracy was within ±25%. CONCLUSIONS A TOF scan method allowed the use of the generic method without compound‐specific optimization and was an alternative choice for routine high‐throughput quantitation of small molecules. The MRM‐HR method on the QqTOF showed good sensitivity which was comparable to that obtained by the MRM method on the triple quadrupole mass spectrometer. Copyright © 2012 John Wiley & Sons, Ltd.